Diagnostic and predictive value of N: L ratio for severity of acute appendicitis - Somnath Biswas; Indranil Halder; Mintu Mohan Nandi; Shanmugam Karthick; Mohan Pradhan (Asian Journal of Medical Sciences, 2025)
Background: The most frequent surgical emergency in clinical practice is acute appendicitis (AA), which has a lifetime incidence of about 7% per person. In the past, appendectomy was the gold standard for treating AA; however, in recent years, this conventional paradigm of therapy has faced significant challenges. Aims and Objectives: To analyze the neutrophil-to-lymphocyte ratio’s (NLR) diagnostic and predictive utility in measuring the severity of AA, as well as its potential as a biomarker for distinguishing between individuals with severe and simple appendicitis. Materials and Methods: This retrospective study was conducted over a period of 1 year and included a total of 280 patients. Results: According to the criteria in methods, a total of 280 cases of AA patients enrolled in the study period. 154 were male and 126 were female. The ages range from 18 to 70 years old with the mean age of 38.56±15.34 years old. The duration of the disease was 2–46 h with the mean duration of 26.89±19.45 h 54 cases were identified as perforated patients, and 226 cases were non-perforated patients. Conclusion: According to our findings, the NLR has the potential to be an easy-to-use and reasonably priced biomarker for determining the severity of AA. More severe types, such as perforation or abscess development, are linked to elevated NLR levels.